Application for Introduction of Augmented Reality-Based Transportation Tools for Children - ardhi pradana; Yulian Findawati (Procedia of Engineering and Life Science, 2021)
The introduction of a means of transportation to children can stimulate the brain to imagine and train creativity. With the development of information technology, means of introducing means of transportation can be done using devices such as computers, laptops or smartphones. The development of Augmented Reality technology on smartphones will make it easier for children to get to know several types of transportation that they often encounter. The purpose of writing this article is to create an application for Introduction to Transportation Tools using Augmented Reality technology for children. The method used in making this application of Introduction to Transportation Tools is observation and interviews. The production begins with collecting data on what types of transportation will be made as a model using the Blender software. Augmented Reality application design uses Unity software by designing markers made from the Vuforia platform. The features in this application are several types of transportation that are displayed in 3D with sound and information using Augmented Reality technology. The results of testing the Transportation Tool Introduction application can run on various Android mobile devices. It has been tested on several different smartphone brands and specifications - the results of the Transportation Tool Introduction can run smoothly except under Android version 4.3 (Jellybean). Based on the test results contained in the Application of Introduction to Transportation Tools using Augmented Reality, it is suitable for introducing more interesting and innovative types of transportation to early childhood. There are still many deficiencies that can be developed, for example, increasing the number of 3D objects in the transportation tool and making animations even better, so that the application is more interesting, interactive, and easy to understand.